Sustainability outcomes of aquaculture eco‐certification: Challenges and opportunities. (7th December 2022) - Rector, Megan E.; Filgueira, Ramon; Bailey, Megan; Walker, Tony R.; Grant, Jon
Abstract: Both the aquaculture industry and eco‐certification of aquaculture have grown significantly over the past 20 years, but the extent to which aquaculture eco‐certification is effective in creating positive environmental and societal outcomes is uncertain. Therefore, a scoping review of research on the effectiveness of eco‐certification in improving aquaculture sustainability outcomes, based on systematic search and inclusion criteria, was conducted. Challenges in producing sustainability outcomes through eco‐certification were identified, including (1) choosing which components of sustainability to reflect in eco‐certification criteria, (2) the risk of limiting improvements in sustainability by labelling a product 'sustainable', (3) accounting for different spatial scales of aquaculture effects, and (4) designing and applying sustainability criteria that work across different local environments. Potential approaches to these challenges include applying an ecosystem services framework to the identification of issues that could be addressed by eco‐certification criteria, supporting continuous improvement of industry best practices, incorporating criteria related to the far‐field effects of aquaculture, and recognising and accounting for the impact of local conditions on farming and eco‐certification. Although alternate governance approaches may be better suited to ensuring improved sustainability outcomes, potential improvements to eco‐certification criteria and processes are presented as opportunities to match the effectiveness of eco‐certification in creating positive sustainability outcomes to its success in creating a market for eco‐certified farmed seafood. However, some of these improvements may require the addition of criteria or complexity within the eco‐certification process, and their impact on market outcomes, particularly the participation of producers, should be considered.